Isolates of the Nematophagous Fungus Pochonia chlamydosporia Are Endophytic in Banana Roots and Promote Plant Growth - Cristina Mingot-Ureta; Federico Lopez-Moya; Luis Vicente Lopez-Llorca (Agronomy, 2020)
The biocontrol fungus Pochonia chlamydosporia colonizes banana roots endophytically. Root hairs and root surface were colonized by a stable GFP (green fluorescent protein) transformant of the fungus. Hyphal penetration in root cells was also observed. Spores of P. chlamydosporia 123, significantly increase root and leaf length and weight in banana plantlets (Musa acuminata cv. ‘Dwarf Cavendish’) in growth chamber experiments 30 days post-inoculation. In greenhouse 8-L pot experiments, P. chlamydosporia 123 spore inoculation significantly increases root, corm and leaf length, and leaf weight in banana plants (75 days post-inoculation). Spore inoculation of P. chlamydosporia strains from diverse origin (Pc21, Pc123, Pc399, and Pccat), significantly increase root, corm and leaf length and weight in banana plantlets. Pc21 from Italy was the best colonizer of banana roots. Consequently, this strain significantly increases banana root and leaf length most. Root colonization by P. chlamydosporia was also detected using cultural techniques and qPCR.